Analisis Gaya Bahasa Dalam Lirik Lagu “Komang” Raim Laode - Setiani, Novi; Izhar , Izhar; Fitriati , Siti (PT. ALHAFI BERKAH INDONESIA, 2023)
This research was conducted to determine the type of language style used in the lyrics of the song